2014
DOI: 10.15570/actaapa.2014.11
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk assessment in HIV-infected male patients: a comparison of Framingham, SCORE, PROCAM and DAD risk equations

Abstract: Introduction: Traditional cardiovascular (CVD) risk assessment algorithms such as the Framingham Risk Score (FRS), Systematic Coronary Risk Evaluation (SCORE) and Prospective Cardiovascular Munster (PROCAM) were developed for general populations, their usefulness in HIV-infected population has not been confirmed. DAD algorithm was developed specifically for HIV-infected patients. The aim of our study was to evaluate the performance of risk assessment algorithms in HIV-infected population. Methods: A prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
5
17
1
4
Order By: Relevance
“…SCORE and FRS have been rarely compared in PLHIV. In a study it was found that SCORE and D:A:D equations were superior to FRS in estimating CVD risk in PLHIV [48]but, in another study conducted in HIV-infected individuals in the USA, it was found that FRS accurately estimated risk of CVD events, D:A:D underestimated risk whereas SCORE performed poorly [49]. However, SCORE equations have been developed and validated in European cohorts and thus they may be more appropriate for using in a European country.…”
Section: Hiv-infected Predicted % (95% Ci)mentioning
confidence: 99%
“…SCORE and FRS have been rarely compared in PLHIV. In a study it was found that SCORE and D:A:D equations were superior to FRS in estimating CVD risk in PLHIV [48]but, in another study conducted in HIV-infected individuals in the USA, it was found that FRS accurately estimated risk of CVD events, D:A:D underestimated risk whereas SCORE performed poorly [49]. However, SCORE equations have been developed and validated in European cohorts and thus they may be more appropriate for using in a European country.…”
Section: Hiv-infected Predicted % (95% Ci)mentioning
confidence: 99%
“…A newly developed score developed for HIV+ patients, the DAD score, has added length of ART treatment and the exposure to certain drugs (abacavir, indinavir, lopinavir) to traditional risk factors. Three studies have compared Framingham risk scores (FRS) to the DAD score [98100], as well as to the FRS with aggravating factors [99], Systematic Coronary Risk Evaluation (SCORE)[100], and Prospective Cardiovascular Munster (PROCAM) score [99, 100] in HIV-infected individuals. Although results from these studies were inconsistent due to differences in study population characteristics, all three studies found fair to good agreement (range 32.5 to 77.4%) among these scores but mostly low (range −0.045 to 0.533) kappa values.…”
Section: Clinical Considerations In Managing Cardiovascular Disease Rmentioning
confidence: 99%
“…O baixo risco de DCV indicado pelo escore de Framingham encontrado em nossa amostra corrobora dados da literatura 35 . O mesmo pode ser justificado pela menor acurácia dos tradicionais escores de risco para DCV em PVHA 36 .…”
Section: Discussionunclassified